Mitotherapy attenuates sepsis-induced brain injury in rats subjected to cecal ligation and puncture: Role of SIRT-1/PGC-1α network - Behnaz Mokhtari; Alireza Alihemmati; Soleyman Bafadam; Solmaz Boraghi; Reza Badalzadeh; Ata Mahmoodpoor (Iranian Journal of Basic Medical Sciences)
Objective(s): Sepsis-induced brain injury poses a critical challenge with limited therapeutic options. Mitochondrial dysfunction is a central contributor to this pathogenesis. The current work aimed to examine the effects of mitochondrial transplantation, termed “mitotherapy”, on sepsis-induced brain injury using a cecal ligation and puncture (CLP) rat model.Materials and Methods: Male Wistar rats (n=40, 12 weeks old, weighing 250–300 g) were allocated into groups with or without CLP-induced sepsis, receiving mitotherapy via single or two repetitive injections post-CLP. In recipient groups, mitochondria harvested from donor rats were injected intravenously (400 μl of mitochondrial suspension containing 7.5×106 mitochondria/ml of respiration buffer). Twenty-four hours post-operation, the behavioral phenotype was tested by using the Murine Sepsis Score (MSS). Brain morphological examination was conducted using Hematoxylin and Eosin staining. Mitochondrial function was measured by evaluating membrane potential, reactive oxygen species production, and adenosine triphosphate content. The expression of genes regulating mitochondrial biogenesis (SIRT-1, PGC-1α) and fission/fusion (Drp1, Mfn1, Mfn2) was determined via real-time polymerase chain reaction. The levels of inflammatory cytokines (TNF-α, IL-1β, IL-6) were measured using Enzyme-Linked Immunosorbent Assay. Results: Mitotherapy reduced MSS and alleviated histopathological changes associated with sepsis-induced brain injury. Furthermore, it restored mitochondrial functional indices, up-regulated genes involved in mitochondrial biogenesis and fusion, and reduced inflammatory cytokine levels (P<0.05). Repetitive injections provided greater therapeutic benefits than a single injection.Conclusion: Mitotherapy mitigated sepsis-induced brain injury by improving mitochondrial function, biogenesis, and dynamics within the SIRT-1/PGC-1α network and concurrently suppressing inflammation. Repetitive injections exhibited enhanced potency, suggesting a novel avenue for managing sepsis-associated brain dysfunction.